Socio-Economic Factors That Influence Recidivism in Kakamega County, Kenya - Oruta, Evans Makori (2016)
Recidivism is the relapse into criminal activity and is generally measured by a former prisoner’s return to prison for a new offence. The rate of recidivism in Kenya is estimated to be about two‐thirds, which means that two‐thirds of released inmates will be re‐incarcerated after their release from prisons. As a result of this, crime by former inmates alone account for a substantial share of the current and future crimes. From the trend in the high prevalence of recidivism in Kenya, there is a staggering high number of people being incarcerated and eventually released back to the community and the high risk of re-arrest and re-incarceration is a concern for policymakers, criminologists, and those involved in corrections. High rates of recidivism result in tremendous costs both in terms of public safety and in monies spent to arrest, prosecute, and incarcerate re‐offenders. High rates of recidivism also lead to devastating social costs to the communities and families of offenders, as well as the personal costs to the offenders themselves. A sample of 146 respondents comprising male and female recidivists at Kakamega and Shikusa Prisons in Western Kenya were considered for the study. Research objective and hypothesis were formulated based on the study constructs. A standard questionnaire was used to collect data from the respondents who were identified using purposive sampling technique. Both quantitative and qualitative data was collected and analyzed. Statistically quantitative data was analyzed using inferential statistics. Findings revealed a statistically significant relationship between socio-economic factors and recidivism. This implied that socio-economic factors such as gender, age, level of education, employment status and housing influence the possibility of re-offending. Therefore the need to come up with working pre-release programs meant to enable inmates to have smooth transitions from correctional institutions to their communities by working with the offenders to develop plans, including housing, employment and participation in post-release programs. Keywords: Socio-Economic Factors, Recidivism, Prison